2022
DOI: 10.3389/fphys.2022.855266
|View full text |Cite
|
Sign up to set email alerts
|

Light Color and the Commercial Broiler: Effect on Ocular Health and Visual Acuity

Abstract: Light is a critical management factor for broiler production, and the wavelength spectrum, one of its components, can affect bird physiology, behavior and production. Among all the senses, sight is important to birds, and their visual system possess several adaptations that allow them to perceive light differently from humans. Therefore, it is critical to consider whether the exposure to monochromatic light colors influences broiler visual ability, which could affect behavioral expression. The present study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…This belief likely originates from considering humans' spectral sensitivity, where humans may not see as well when exposed to a short wavelength compared to white light. However, previous research demonstrated that when broilers are raised under blue light, they have improved spatial vision and minor changes in refraction index and eye health ( Remonato Franco et al, 2022a ). Therefore, poor vision is likely not the reason for any observed behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…This belief likely originates from considering humans' spectral sensitivity, where humans may not see as well when exposed to a short wavelength compared to white light. However, previous research demonstrated that when broilers are raised under blue light, they have improved spatial vision and minor changes in refraction index and eye health ( Remonato Franco et al, 2022a ). Therefore, poor vision is likely not the reason for any observed behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…Poultry have a more sensitive vision system than humans, with the ability to perceive a broader range of colors, a wider field of vision, and greater sensitivity to visual harmony (Prescott, et al, 2003;Remonato Franco, et al, 2022). Different wavelengths of light have various stimulatory effects on the eye retina, which induces many changes in poultry behavior and growth (Lan, et al, 2013).…”
Section: Poultry Spectral Sensitivitymentioning
confidence: 99%